Multi-stakeholder Perspectives on the Maternal, Provider, Institutional, Community, and Policy Drivers of Disrespectful Maternity Care in South-East Nigeria - Okedo-Alex IN; Akamike IC; Nwafor JI; Abateneh DD; Uneke CJ (Dove Medical Press, 2020)
Ijeoma Nkem Okedo-Alex,1,2 Ifeyinwa Chizoba Akamike,1,2 Johnbosco Ifunanya Nwafor,3 Dejene Derseh Abateneh,4 Chigozie Jesse Uneke2 1Department of Community Medicine, Alex Ekwueme Federal University Teaching Hospital, Abakaliki, Ebonyi State, Nigeria; 2African Institute for Health Policy and Health Systems, Ebonyi State University (EBSU), Abakaliki, Nigeria; 3Department of Obstetrics and Gynaecology, Alex Ekwueme Federal University Teaching Hospital, Abakaliki, Ebonyi State, Nigeria; 4Department of Medical Laboratory Sciences, Menelik II College of Medicine and Health Sciences, Kotebe Metropolitan University, Addis Ababa, EthiopiaCorrespondence: Ijeoma Nkem Okedo-AlexAfrican Institute for Health Policy and Health Systems, Ebonyi State University (EBSU), Abakaliki, NigeriaEmail ijeomaninadr@gmail.comDejene Derseh AbatenehDepartment of Medical Laboratory Sciences, Menelik II College of Medicine and Health Sciences, Kotebe Metropolitan University, Addis Ababa, EthiopiaTel +251920514158Email dejenieh@gmail.comPurpose: Understanding the contextualized perspectives of stakeholders involved in maternal health care is critical to promoting respectful maternity care. This study explored maternal, provider, institutional, community, and policy level drivers of disrespectful maternity care in Southeast Nigeria. This study also identified multi-stakeholder perspectives on solutions to implementing respectful maternity care in health facilities.Materials and Methods: This was a mixed-methods cross-sectional study conducted in two urban cities of Ebonyi State, South-eastern Nigeria. Data were collected using semi-structured questionnaires, focus group discussions, and key informant interviews with mothers, providers, senior facility obstetric decision-makers, ministry of health policymaker, and community members. Quantitative data and qualitative data were analysed using SPSS version 20 and manual thematic analysis, respectively.Results: Maternal level drivers were poor antenatal clinic attendance, uncooperative clients, non-provision of birthing materials, and low awareness of rights. Provider factors included work overload/stress, training gaps, desire for good obstetric outcome, under-remuneration and under-appreciation. Institutional drivers were poor work environments including poorly designed wards for privacy, stressful hospital protocols, and non-provision of work equipment. Community-level drivers were poor female autonomy, empowerment, and normalization of disrespect and abuse during childbirth. The absence of targeted policies and the high cost of maternal health services were identified as policy-related drivers.Conclusion: A variety of multi-level drivers of disrespectful maternity care were identified. A diverse and inclusive multi-stakeholder approach should underline efforts to mitigate disrespectful maternity care and promote respectful, equitable, and quality maternal health care.Keywords: respectful maternity care, disrespect and abuse during childbirth, facility-based childbirth, drivers, Nigeria